2011
DOI: 10.1038/nm.2324
|View full text |Cite
|
Sign up to set email alerts
|

A reversible form of axon damage in experimental autoimmune encephalomyelitis and multiple sclerosis

Abstract: In multiple sclerosis, a common inflammatory disease of the central nervous system, immune-mediated axon damage is responsible for permanent neurological deficits. How axon damage is initiated is not known. Here we use in vivo imaging to identify a previously undescribed variant of axon damage in a mouse model of multiple sclerosis. This process, termed 'focal axonal degeneration' (FAD), is characterized by sequential stages, beginning with focal swellings and progressing to axon fragmentation. Notably, most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
660
6
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 652 publications
(740 citation statements)
references
References 40 publications
61
660
6
13
Order By: Relevance
“…This may be due to lysolecithin‐induced depletion of myelin‐derived trophic support to axons, which in the case of already damaged P301S‐htau axons resulted in marked degeneration. Indeed Nikic et al(2011) have described that in an experimental model of MS axons showing signs of injury such as swelling and dystrophic mitochondria, can recover if they retain the myelin wrapping. To determine whether the axonal degeneration observed in P301S‐htau mice may have influenced the OPCs maturation in vivo , we investigated the functionality of OPCs isolated from 10‐ to 12‐day old mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to lysolecithin‐induced depletion of myelin‐derived trophic support to axons, which in the case of already damaged P301S‐htau axons resulted in marked degeneration. Indeed Nikic et al(2011) have described that in an experimental model of MS axons showing signs of injury such as swelling and dystrophic mitochondria, can recover if they retain the myelin wrapping. To determine whether the axonal degeneration observed in P301S‐htau mice may have influenced the OPCs maturation in vivo , we investigated the functionality of OPCs isolated from 10‐ to 12‐day old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, enhancing remyelination, and particularly OPC differentiation, is an important therapeutic strategy to promote neuroprotection in the progressive stage of MS. Injured axons in the MS lesion initially show a focal mitochondrial dysmorphism and axonal swelling (Nikic et al, 2011) which subsequently develops into axonal truncation with terminal ovoids (Trapp et al, 1998). Injured axons in MS lesions accumulate amyloid precursor protein (APP), which is detectable only in axons with impaired fast axonal transport (Ferguson et al, 1997; Sherriff et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percentage of cell loss was defined as percentage of cells that lost >50% of their fluorescence, which was accompanied by clear changes in morphology (rounding, process blebbing). Axon morphology in a neuroinflammatory setting was staged as described previously 21, 22. Only axons that were observable across all time points during the experiment over at least 50 µm were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we use an in vivo two‐photon imaging approach to the mouse spinal cord that we previously established20, 21, 22 to gain insight into AQP4‐Ig‐mediated lesion formation. We found that AQP4‐Ig‐containing samples obtained from NMO patients (as well as a recombinant AQP4‐IgG from a clonotypic plasma blast present in the CSF of an NMO patient) caused acute, dose‐dependent and (human) complement‐mediated loss of astrocytes when applied at the pial surface of the spinal cord at IgG concentrations found intrathecally in NMO 23.…”
mentioning
confidence: 99%